Pengembangan E-Modul Berbasis Canva pada Mata Pelajaran OTK Sarana dan Prasarana di SMKN 40 Jakarta - Puput Putry El Mushan; Roni Faslah; Marsofiyati Marsofiyati (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is to determine the feasibility and practicilaty of developing Canva-Based E-Modul in the Subjcet of Facilities and Insfrastucture. This research was conducted at SMKN 40 Jakarta in class XI OTKP with 36 students. This research uses the method of Research and Decelopment (RnD) with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. The research subjects comprised three validators (material experts, linguists, and media expert) and 36 students of class XI OTKP. The method use in this research is the qualitative method. The data collection technique used was a questionnaire with a likert scale of 1-5. The data analysis technique used was an expert validation test and practicality test. Material experts carried out expert validation test with a percentage of 91% which was categorized as very feasible, linguist with a percentage of 98% which was categorized as very feasible, and media experts with a percentage of 86% whis was categorized as very feasible. In the practicality test conducted by 36 students of class XI OTKP, at stage one-to-one evaluation with a percentage of 91% which was categorized as very practical, at the small group trial stage with a percentage of 90% which was categoized as very practical, and the large group trial stage with a percentage of 92% which was categorized as very practical. The result of this research and development indicate that the Development of Canva-Based E-Module in the Subject of Facilities and Infrastructure at SMKN 40 Jakarta is stated to be very feasible and very practical, and can be used in learning activities.